Religious affects: animality, evolution, and power - Schaefer, Donovan O. (Duke University Press, 2015)
Religion, language, and affect -- Intransigence : power, embodiment, and the two types of affect theory -- Teaching religion, emotion, and global cinema -- Compulsion : affect, desire, and materiality -- Savages : ideology, primatology, and Islamophobia -- Accident: animalism, evolution, and affective economies -- A theory of the waterfall dance : on accident, language, and animal religion